A new species of Gladiovalva Sattler, 1960 from Central Asia (Lepidoptera: Gelechiidae) - Oleksiy Bidzilya; Jan Sumpich (SHILAP)
Re-examination of museum’s vouchers of Gladiovalva igorella Falkovitsh & Bidzilya, 2003 resulted in the discovery of new, hitherto undescribed species, which is in this paper described as Gladiovalva arevika Bidzilya & Sumpich, sp. n. Photographs of its adults and genitalia of both sexes are presented as well as the comparison with those of G. igorella.